Comparative study of the influence of diabetes distress and depression on treatment adherence in Chinese patients with type 2 diabetes: a cross-sectional survey in the People's Republic of China - Xu, Cuiping; Zhang; Li, Yan; Liu, Qing-zhi; Wu, Hong-xia; Xu, Ze-jun; Xue, Xiu-juan; Gao, Qing (Neuropsychiatric disease and treatment, 2013)
The purpose of this study was to explore diabetes-related distress and depression and their influence on treatment adherence in Chinese patients with type 2 diabetes. We surveyed 200 type 2 diabetic patients from two public hospitals using the Diabetes Distress Scale (DDS), Zung Self-rating Depression Scale, and Revised Treatment Adherence in Diabetes Questionnaire (RADQ). A multiple regression model was used to explore the relationship between diabetes distress, depression, and treatment adherence. In the 200 eligible patients, the incidence of depression and diabetes distress was approximately 24% and 64%, respectively. The mean score on the RADQ was 23.0 ± 6.0. Multiple regression analysis showed that DDS scores (β = 5.34, P = 0.000), age (β = 0.15, P = 0.014), and family history (β = 3.2, P = 0.016) had a positive correlation with depression. DDS scores (β = -2.30, P = 0.000) and treatment methods (β = -0.93, P = 0.012) were risk factors for poor treatment adherence, whereas age (β = 0.089, P = 0.000) and cohabitation (β = 0.93, P = 0.012) increased treatment adherence. The independent-samples t- test showed that depression also affected treatment adherence (t = 2.53, P < 0.05). These findings suggest that the DDS is a predictor of depression and that diabetes distress plays a more important part than depression in treatment adherence. Screening for diabetes distress may be useful for primary prevention of psychologic problems; however, some form of specialized psychologic intervention should be incorporated to promote patient adherence with treatment.